Financing the operation and maintenance costs of hurricane protection infrastructure : options for the state of Louisiana - Miller, Trey (RAND, 2012)
This report analyzes the fiscal capacity of eight local levee districts in southern Louisiana to shoulder the burden of operating and maintaining the Hurricane and Storm Damage Risk Reduction System (HSDRRS) and other key hurricane protection infrastructure currently under construction by the U.S. Army Corps of Engineers. It specifically focuses on operation and maintenance (O & M) costs, assuming that costs associated with major repairs and levee lifts will not be borne by levee districts. It also discusses some innovative approaches that other government agencies responsible for operating and maintaining flood and hurricane protection infrastructure are using to generate revenue to cover those costs. The report discusses the methodology used to project the O & M costs associated with hurricane protection infrastructure. It provides O & M cost estimates for each newly constructed piece of the HSDRRS and estimates the total O & M costs to be borne by eight major levee districts within the HSDRRS. Some of these estimates differ from estimates based on cost-plus engineering estimates because they are based on historical expenditures by levee districts to maintain existing infrastructure. The report then discusses the author's methodology for projecting levee district budget revenues and budget balances through 2016. The report concludes with a discussion of some options that other states have used to generate revenue for the O & M of levees and hurricane protection infrastructure.